A retrospective cohort study to investigate fatigue, psychological or cognitive impairment after TIA: protocol paper. Issue 4 (3rd May 2015) - Moran, Grace M; Calvert, Melanie; Feltham, Max G; Ryan, Ronan; Marshall, Tom
Abstract : Introduction: Transient ischaemic attack (TIA) is defined by short-lasting, stroke-like symptoms, and is recognised as a medical emergency. Symptoms are assumed to completely resolve, and treatment is focused on secondary stroke/TIA prevention. However, evidence suggests that patients with TIA may experience ongoing residual impairments, which they do not receive therapy for as standard practice. TIA-induced sequelae could impact on patients' quality of life and ability to return to work or social activities. We aim to investigate whether TIA is associated with subsequent consultation for fatigue, psychological or cognitive impairment in primary care. Methods and analysis: A retrospective open cohort study of patients with first-ever TIA and matched controls. Relevant data will be extracted from The Health Improvement Network (THIN) database, an anonymised primary care database which includes data for over 12 million patients and covers approximately 6% of the UK population. Outcomes will be the first consultation for fatigue, anxiety, depression, post-traumatic stress disorder or cognitive impairment. Principal analysis will use Kaplan-Meier survivor functions to estimate time to first consultation, with log-rank tests to compare TIA and control patients. Cox proportional hazard models will predict the effect of demographic and patient characteristics on time to first consultation. Ethics and dissemination: Approval was granted by a THIN Scientific Review Committee (ref: 14-008). The study's findings will be published in a peer-reviewed journal and disseminated at national and international conferences and through social media.